Effectiveness of paediatric asthma clinical pathways: a narrative systematic review. (June 2014) - Chen, Kee-Hsin; Chen, Chiehfeng (Cliff); Liu, Hsueh-Erh; Tzeng, Pei-Chuan; Glasziou, Paul P.
Abstract Objective: To evaluate the effectiveness of clinical pathways (CPs) for paediatric asthma on length of hospital stay, additional visits due to asthma exacerbations, hospital cost, manpower and workload required for implementing CPs. Methods: Studies were eligible if they met the following criteria: children (≦18 years) with asthma, hospital or emergency department based, and study designs were (1) randomised controlled trial, (2) controlled clinical trial or (3) controlled before and after study. Two reviewers independently screened references, extracted data and assessed the risk of bias. We resolved disagreement by discussion between authors. Due to an insufficient number of studies and the heterogeneity of interventions and outcomes, we conducted a narrative systematic review with forest plots but did not pool results. Results: About 3155 relevant articles were identified through a literature search, 628 were duplicates removed, 2037 were excluded based on review of titles and abstracts and 117 were excluded because they did not meet inclusion criteria. Seven studies involving 2600 participants met the inclusion criteria. Using asthma CPs may decrease the length of hospital stay; however, CPs did not appear to reduce additional visits due to asthma exacerbations or reduce hospital costs. No eligible studies were found that quantified the manpower and workload for implementing CPs. Conclusions: Current studies suggest CPs may reduce the length of hospital stay, but insufficient evidence is available on total costs or readmissions to justify extensive uptake of asthma CPs in paediatric inpatient care. Higher quality, large randomised controlled trials are required that measure costs and a wider range of outcomes.